Genomics Tools to Study Membrane-Based Systems - Ali, Muhammad (My University, 2024)
The learning objectives of this chapter are the following: - Designing an experimental plan for omics-based study for membrane-based systems - Omics tools to investigate microbial communities of membrane-based systems - Introduction to state-of-the-art bioinformatics tools and reference database resources - Application of genome-resolved metatranscriptomics approach to study the activity of microorganisms
Experimental Methods for Membrane Applications in Desalination and Water Treatment
Keywords: International Development; Manuscript, Book and Print Cultures; Civil Engineering; Environmental Impacts, Interactions; Environmental engineering